High-temperature modification of sibunit for its application as a support for ruthenium catalysts in ammonia synthesis; AIP Conference Proceedings; Vol. 2141 : Oil and Gas Engineering (OGE-2019) - Borisov V. A.; Iost K. N.; Temerev V. L.; Surovikin Y. V.; Smorokov A. A. Andrey Arkadievich; Fedotova P. A.; Shlyapin D. A. (2019, 2019)
Title screen